2017
DOI: 10.3892/mmr.2017.8017
|View full text |Cite
|
Sign up to set email alerts
|

D‑Tagatose inhibits the growth and biofilm formation of Streptococcus�mutans

Abstract: Dental caries is an important global health concern and Streptococcus mutans has been established as a major cariogenic bacterial species. Reports indicate that a rare sugar, D-tagatose, is not easily catabolized by pathogenic bacteria. In the present study, the inhibitory effects of D-tagatose on the growth and biofilm formation of S. mutans GS-5 were examined. Monitoring S. mutans growth over a 24 h period revealed that D-tagatose prolonged the lag phase without interfering with the final cell yield. This gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…Tagatose is a rare sugar that can be metabolized by only certain microbial taxa (Raichand et al, 2012;Martinussen et al, 2013;Van Der Heiden et al, 2013;Wu and Shah, 2017) and inhibits some important crop pathogens, P. infestans included (Ohara et al, 2008). Nutritional and anti-nutritional effects of tagatose have been shown on human-associated microorganisms (Van Der Heiden et al, 2013;Lobete et al, 2017;Wu and Shah, 2017;Hasibul et al, 2018) and plant-associated microorganisms (Komon-Zelazowska et al, 2007;Izumori et al, 2008;Ohara et al, 2008;Hayer et al, 2013;Perazzolli et al, 2020). We showed that tagatose inhibited the growth of P. infestans, but it had only slight effects on P. cinnamomi, with a species-specific impact on the mitochondrial processes.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Tagatose is a rare sugar that can be metabolized by only certain microbial taxa (Raichand et al, 2012;Martinussen et al, 2013;Van Der Heiden et al, 2013;Wu and Shah, 2017) and inhibits some important crop pathogens, P. infestans included (Ohara et al, 2008). Nutritional and anti-nutritional effects of tagatose have been shown on human-associated microorganisms (Van Der Heiden et al, 2013;Lobete et al, 2017;Wu and Shah, 2017;Hasibul et al, 2018) and plant-associated microorganisms (Komon-Zelazowska et al, 2007;Izumori et al, 2008;Ohara et al, 2008;Hayer et al, 2013;Perazzolli et al, 2020). We showed that tagatose inhibited the growth of P. infestans, but it had only slight effects on P. cinnamomi, with a species-specific impact on the mitochondrial processes.…”
Section: Discussionmentioning
confidence: 48%
“…and Lactobacillus spp. (Bertelsen et al, 1999;Vastenavond et al, 2011;Hasibul et al, 2018). On the other hand, tagatose inhibits the growth of human pathogenic bacteria, such as Streptococcus mutants and Salmonella enterica serovar Typhimurium (Lobete et al, 2017;Hasibul et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that sulfur-containing compounds derived from garlic, such as diallyl disulfide (DAS 2 ) and ajoene, inhibit biofilm formation and the QS of bacteria, even though the antimicrobial activities of these compounds are lower than those in medical antibiotics used in clinical settings (11)(12)(13)(14)(15)(16). Furthermore, Slachmuylders et al and others have demonstrated that some natural products, which exert an inhibitory effect on biofilm formation, have antibiotic-potentiating activity (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Plaque bio¯lm is composed of cells and extracellular matrix composing of proteins and extracellular polysaccharides, which enhances the adhesion and cohesion of the bio¯lm, protects the attached bacteria, and promotes the local Pondus Hydrogenii (PH) reduction to form an acidic environment. 1,2 In clinical methods, in addition to physical removal of bio¯lms, chemical methods to kill bacteria in bio¯lms have been the focus of people's research. General methods include the use of antibiotics and chemical oxidants, but both have their drawbacks.…”
Section: Introductionmentioning
confidence: 99%